Climate Risk Management in Agricultural Extension (CRMAE) for Ethiopia’s Agricultural Technical Vocational Education and Training (ATVET) Program - Grossi, Amanda; Dinku, Tufa; Hansen, James; Trzaska, Sylwia; Nsengiyumva, Gloriose (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
A two-day consultative workshop was implemented from March 14-15, 2022, in Bishoftu, Ethiopia by the International Research Institute for Climate and Society (IRI) of the Columbia Climate School. The workshop, which was organized as part of the World Bank’s Accelerating the Impact of CGIAR Climate Research for Africa (AICCRA) project and in close collaboration with the Adapting Agriculture to Climate Today, for Tomorrow (ACToday) Columbia World Project, brought together various professionals from the Ministry of Agriculture (MoA), the Ministry of Skills and Labor (MosL), and Agricultural Technical and Vocational Education and Training (ATVET) colleges to review a proposed unit of competence and associated materials on Climate Risk Management in Agricultural Extension (CRMAE) for inclusion in Ethiopia’s ATVET training program curriculum.